Bio‐oil upgrading via ketonization of carboxylic acids on Na promoted Ca/AlOx catalysts. Issue 1 (14th July 2022) - Wang, Zichun; Arstad, Bjørnar; Wang, Leizhi; Ling, Huajuan; Shi, Jeffrey; Stampfl, Catherine; Jiang, Yijiao; Huang, Jun
Abstract: Ketonization of carboxylic acids is valuable for bio‐oil upgrading and producing bio‐derived chemicals. Ca/AlOx metal oxides with various Ca/Al ratios have been prepared by the low‐cost and natural abundant metals in the process. The addition of alkaline or alkaline‐earth metals could significantly improve the activity of Ca/AlOx catalysts by base‐catalyzed ketonization of carboxylic acids. However, the active sites on alkaline‐metal‐doped Ca/AlOx catalysts are still under debate, and the commercialization of these catalysts often suffers from deactivation in long‐term use. Here Ca(Na)/AlOx catalysts with various Ca/Al molar ratios were prepared and evaluated for the ketonization of acetic acid. Sodium addition resulting in the formation of NaAlO2 has higher basicity than CaO. These strong basic sites could significantly promote the ketonization of acetic acid via the thermal decomposition of carboxylates. The Ca(Na)/AlOx catalyst with NaAlO2 populated on the surface could provide 100% acetone selectivity at the complete conversion of acetic acid at 400°C and exhibit no activity loss after a 400 h reaction, which is the most active and stable catalyst for ketonization reaction hitherto. These Ca(Na)/AlOx catalysts are also stable by adding major bio‐oil model compounds (e.g., phenol) into the reaction mixture, which are promising for future bio‐oil upgrading applications. Abstract : Alkaline‐metal addition can improve the activity of Ca/AlOx catalysts by base‐catalyzed ketonization of carboxylic acids for bio‐oil upgrading and producing bio‐derived chemicals. The commercialization of these catalysts suffers from unclear active sites and significant deactivation in long‐term use. Here the NaAlO2 populated Ca(Na)/AlOx catalyst can provide 100% acetone selectivity at the complete conversion of acetic acid at 400°C and exhibit no activity loss after 400 h reaction, which is the most active and stable catalyst for ketonization reaction hitherto.